Income taxation and the validity of state capacity indicators. (4th November 2013) - Rogers, Melissa Ziegler; Weller, Nicholas
Abstract State capacity is a key concept for research in public policy and political science. Despite its importance, there is no broadly accepted measure of state capacity in the existing literature, and frequently used measures of capacity have not been examined for their validity. We begin with an explicit definition of state capacity – the state's ability to implement public policy – and connect this definition to a measurable outcome of state capacity – the state's taxation of income. We show that this measure, income taxes as a percentage of total tax revenue, is a useful indicator of state capacity and meets higher standards of measurement validity than other tax-based indicators. We also compare our measure to the most common existing indicators of state capacity to show that income taxation is a better theoretical and statistical measure of states' effectiveness in policy implementation.